Dinamika Social Commerce Industri Kecantikan: Content Marketing dan TikTok Live Streaming Memacu Keputusan Pembelian Gen Z Melalui Brand Awareness - Ahmad Zaki; Veronica Kireina Hana Kristiani (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
The rapid development of social commerce has shifted consumer shopping behavior, particularly among Generation Z in the beauty industry. This study aims to examine the effect of content marketing and live streaming on purchase decisions, with brand awareness as a mediating variable for Camille Beauty products on the TikTok platform. A quantitative approach was employed, involving 100 Generation Z respondents in Indonesia selected through purposive sampling, specifically users who had made a purchase after being exposed to the brand's promotional content and live broadcasts. Primary data were collected via online questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.1 software. The findings demonstrate that content marketing and live streaming have a positive and significant direct effect on both brand awareness and purchase decisions. Furthermore, brand awareness significantly mediates the relationship between these two digital marketing strategies and the purchase decision. Based on these findings, it is recommended that Camille Beauty optimize its content strategy by presenting more up-to-date product information, provide capacity-building training for live stream hosts to be more interactive and responsive to the audience, and strengthen brand identity to drive higher sales conversions.